Podstawowe formy prawne działania administracji publicznej na rzecz ochrony zwierząt - Jedlecka, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In the protection of animals an administrative act in the form of the administrative decision is adominating legal form of action of public administration. Acts of the local law play an important role. For example, catching homeless animals takes place only based on the resolution of the commune council. Rarely are used other legal forms of action of the public administration, like material-technical activity, social-organizational activity or civil law agreements.
Keywords: okrucieństwo wobec zwierząt; ochrona prawna zwierząt; administracyjny akt; decyzja administracyjna; akty prawa lokalnego